Law Enforcement Against Criminal Acts of Online Gaming In The City of Surabaya - Flavia Irene Iswahyudi (Faculty of Law, Merdeka University Surabaya, 2022)
purpose of doing research on law enforcement against online gambling crime is to find out the form of law enforcement, especially in the city of Surabaya. The research method used by the author is a normative research method, the author collects some data to be used to answer the problem formulation, which comes from from laws and regulations, books or literature, journals, and official documents. The results of the study can be concluded that in the enforcement of criminal law, there are two ways in carrying out countermeasures. In carrying out the first countermeasures, using penal law enforcement, and the second countermeasures using non-penal law enforcement. Law enforcement against online gambling uses penal countermeasures, where the process is the same as other criminal acts, starting from the investigation, investigation, to the trial process. In the forms of criminal acts of conventional gambling and online gambling, the contents of the article are not much different. In conventional gambling still uses the traditional way. However, online gambling is much more modern because it uses the internet network and information technology media such as cellphones or laptops. Regulations regarding conventional gambling can be seen in Article 303 or 303 bis of the Criminal Code, while regulations regarding online gambling are regulated in Article 45 paragraph (2) of Law Number 19 of 2016 concerning Electronic Information and Transactions.